STRUCTURAL SYNTHESIS OF A MOBILE FIRE EXTINGUISHER FOR CLASS B FIRE EXTINGUISHING - Abramov, Yu; Kolomiiets, V.; Sobyna, V. (Komunalʹne hospodarstvo mist, 2024)
With regard to a mobile firefighting unit based on a sigway, which is focused on extinguishing class B fires with sprayed water, its functional diagram is constructed. A feature of such a mobile fire-fighting unit is the inclusion of a human operator in its composition. For the set of elements of the mobile fire unit, the expression of the transfer function is obtained, the peculiarity of which is the presence of a lagging link. According to the principle of dynamic compensation, this transfer function is used to form the transfer function of the correction element. The transfer function of the correction element is formed using a priori specified transient quality indicators. Under these conditions, a reference transfer function of a mobile fire unit is chosen, whose Hurwitz polynomial is of the fourth order. It is shown that the transfer function of the correction element can be represented as a fractional rational function, the numerator polynomial of which is of the fourth order and the denominator polynomial of the sixth order. The coefficients of the denominator polynomial are subject to the necessary conditions of the Hurwitz criterion. These coefficients are determined through the generalized delay time of the elements of the mobile fire unit and through the ratio of the dimensionless time of the transient process and its dimensional permissible value. It is shown that the realization of the correction element can be carried out by means of two types of elementary dynamic links - integrating and aperiodic. A verbal interpretation of the algorithm for structural synthesis of a mobile fire unit is given. An example of such a structural synthesis is given and it is shown that the introduction of a correction element into the structure of a mobile fire unit provides a reduction in the time to extinguish a class B fire using sprayed water by an order of magnitude. Keywords: mobile fire extinguishing unit, transfer function, quality indicators, extinguishing time.